1998
DOI: 10.1177/074873098129000192
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of per RNA in Noncoding Regions Affect Periodicity of Circadian Behavioral Rhythms

Abstract: Circadian rhythms in Drosophila depend on a molecular feedback loop that includes products of the period (per) and timeless (tim) genes. RNA and protein products of both genes cycle with a circadian period and the proteins feedback to inhibit expression of their own mRNAs. While cyclic expression of PER protein appears to be necessary for rhythmic behavior, the function of per RNA cycling is somewhat controversial. Rhythmic transcription accounts, in part, for cycling of per RNA, but it is clear now that postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…A later study demonstrated that an element in the 3Ј-UTR of Per1 promotes its instability, thereby contributing to this destabilization (Kojima et al, 2003). The 3Ј-UTRs of other clock genes, such as Drosophila Per, rat Aanat, and mouse Per2, Per3 and Cry1, also contribute to regulating their rhythmic expression, thereby leading to an accurate circadian period (Chen et al, 1998;Kim et al, 2005;Kim et al, 2007a;Kwak et al, 2006;Woo et al, 2010;Woo et al, 2009).…”
Section: Post-transcriptional Regulation In Animalsmentioning
confidence: 99%
“…A later study demonstrated that an element in the 3Ј-UTR of Per1 promotes its instability, thereby contributing to this destabilization (Kojima et al, 2003). The 3Ј-UTRs of other clock genes, such as Drosophila Per, rat Aanat, and mouse Per2, Per3 and Cry1, also contribute to regulating their rhythmic expression, thereby leading to an accurate circadian period (Chen et al, 1998;Kim et al, 2005;Kim et al, 2007a;Kwak et al, 2006;Woo et al, 2010;Woo et al, 2009).…”
Section: Post-transcriptional Regulation In Animalsmentioning
confidence: 99%
“…(The same study also showed that posttranscriptional events are involved in the generation of the mRNA rhythm of a clock-controlled gene called Crg-1.) dPer mRNA contains elements in its 5´and 3´UTRs that affect PER protein cycling and fly behavior, probably through regulation of mRNA stability (Chen et al 1998;Stanewsky et al 2002). Additionally, it has been shown that translation is also under circadian regulation; two alternative splicing variants exhibit different translational properties, and cyclic dPer mRNA is not required for PER protein rhythmicity .…”
Section: Circadian Regulation Of Splicing Variantsmentioning
confidence: 99%
“…In Drosophila, dper mRNA half-life also appears to be regulated by the circadian clock, resulting in different message stability during accumulating and decay phases (20). Also, the circadian cycling of dPER levels depends on the 3Ј UTR of the dper mRNA (21).…”
mentioning
confidence: 99%